Enforcement of The Criminal Act of Embezzlement of Motor Vehicles in the GorontaloCity Jurisdiction - Melly Handayani Dama (Universitas Negeri Gorontalo, 2019)
The purpose of this study is to find out what factors are inhibiting the police in carrying out enforcement of the Motor Vehicle Embezzlement Law in the Gorontalo City Area. This type of research is empirical research, using a qualitative approach,which is analyzed qualitatively descriptively. Based on the results of research shows that law enforcement conducted by the Gorontalo City Resort Police has been based on the prevailing statutory mechanism even though in the implementation of the crime of embezzlement of four-wheeled motor vehicles there are still some cases that can not be resolved due to obstacles to the investigation process. While the factors that inhibit the Police from committing criminal acts of Motor Vehicle Embezzlement are lack of information, lack of witnesses, and lack of public legal awareness.